Determination of Yield, Quality and Chemical Composition of Palm Oil and Palm Kernel Oil of Fresh Fruit Bunches with Variation Maturity as A Basic for Determining Harvest Maturity Standard - Hasibuan, Hasrul Abdi (Jurnal Penelitian Kelapa Sawit, 2020)
Fresh fruit bunches (FFB) maturity greatly affects the yield and quality of crude palm oil (CPO), kernel, and palm kernel oil (PKO). Conventional criteria for mature harvest are still used for determining production targets. These criteria are also used as a basis for developing mechanized and digitalized harvesting technologies. This research was conducted to determine the optimum harvest FFB maturity criteria based on the number of loose fruit from bunches before harvesting, related to the yield, quality, and chemical characteristics of CPO and PKO. Samples used were Tenera type FFBs with the variety of maturity including unripe (reddish black fruit), under-ripe (red fruit but no loose fruit), ripe (loose fruit of 1-3 grains), ripe (loose fruit of 5-10 grains), and overripe (loose fruit of 20-40 grains). The yield of CPO, kernel and PKO increased with increasing fruit maturity. The riper fruit, free fatty acid content and peroxide value of CPO increased. It was also the same for carotene content and deterioration of the bleachability index (DOBI) but the value of both decreased in overripe fruit. The iodine value and fatty acids composition differed of each fruit maturity. Generally, in some Tenera varieties, the average of yield of CPO and kernel, and quality of CPO in ripe fruits (1-3 grains) were relatively same to ripe fruit (loose fruit 5-10 grains). Thus, the optimal yield and quality of CPO, kernel and PKO can be obtained by harvesting of FFB on the mature criteria with a number of loose fruit 1-3 grains.